The Burden of Maternal Mental Health During COVID-19: Impact Analysis Through Perinatal Mood and Anxiety Disorders Screening [A272]. (May 2022) - Brow, Katherine; Kar, Ayesha; Andrews, Celine Marlin; Engel, Casey; Lee, Grace; James, Jaclyn N.
Abstract : INTRODUCTION: The American College of Obstetrics and Gynecology (ACOG) recommends screening for depression and anxiety at least once during the perinatal period and again during postpartum checks. The delivery of validated screening tools varies amongst institutions and individual obstetricians. The objectives of this study were to assess our institution's baseline screening rates and the impact of the COVID-19 pandemic on maternal mental health. METHODS: Our patient population was pregnant and postpartum patients at Carilion Clinic from January 2019 to July 2020. Data collected from medical records included scores of the Edinburgh Perinatal Depression Screening (EPDS), Personal Health Questionnaire (PHQ) 2 and 9, demographics, and psychiatric history. Screening rates and incidence of mood disorders were compared between pre– and intra–COVID-19 cohorts. RESULTS: Of the 850 women included, 43.5% (n=370) were screened during perinatal visits and 49.8% (n=424) postpartum. Screenings were completed more frequently during postpartum checks pre–COVID-19 compared to during the pandemic with PHQ-2 (27.4% vs. 16.1%, P =.0001) and PHQ-9 (10.3% vs. 5.4%, P =.011). More women screened positive for depression at perinatal checks during the pandemic compared to pre-pandemic (13.2% vs. 4.7%, P =.0377). CONCLUSION: The COVID-19 pandemic has affected rates of maternal depression screening and has significant mental health impacts on this population. This study reveals baseline rates of screening in perinatal and postpartum visits at our institution, which is critical to delivery of quality care. This information will help inform strategies to increase rates of screening and ensure that mental health needs are being addressed, especially in times of emergency.